Failure of cargo aileron’s actuator - G. Zucca; M. Amura; L. Allegrucci; M. Bernabei (Fracture and Structural Integrity)
During a ferry flight, in a standard operation condition and at cruising level, a military cargo experienced a double hydraulic system failure due to a structural damage of the dual booster actuator. The booster actuator is the main component in mechanism of aileron’s deflection. The crew was able to arrange an emergency landing thanks to the spare oil onboard: load specialists refilled the hydraulic reservoirs. Due to safety concerns and in order to prevent the possibility of other similar incidents, a technical investigation took place. The study aimed to carry out the analysis of root causes of the actuator failure. The Booster actuator is composed mainly by the piston rod and its aluminum external case (AA7049). The assembly has two bronze caps on both ends. These are fixed in position by means of two retainers. At one end of the actuator case is placed a trunnion: a cylindrical protrusion used as a pivoting point on the aircraft. The fracture was located at one end of the case, on the trunnion side, in correspondence to the cap and over the retainer. One of the two fracture surfaces was found separated to the case and with the cap entangled inside. The fracture surfaces of the external case indicated fatigue crack growth followed by ductile separation. The failure analysis was performed by means of optical, metallographic, digital and electronic microscopy. The collected evidences showed a multiple initiation fracture mechanism. Moreover, 3D scanner reconstruction and numerical simulation demonstrated that dimensional non conformances and thermal loads caused an abnormal stress concentration. Stress concentration was located along the case assy outer surface where the fatigue crack originated. The progressive rupture mechanism grew under cyclical axial load due to the normal operations. Recommendations were issued in order to improve dimensional controls and assembly procedures during production and overhaul activities.